The construction of the narrator in Rubem Fonseca. Analysis of the story "The collector" - Benavides, Jeovanny (2020)
Rubem Fonseca’s narrative is marked by the constant search for destiny and the human condition. His stories and novels deal with topics whose perspectives are oriented towards violence; in addition, his style, direct and unambiguous, has made him a very popular writer in the field of contemporary Latin American literature. In many of his works, this writer creates and recreates a fictional world by the hand of a narrator who is far from social conventions, a marginal who acts detached from the law and seeks to subvert social roles, as in his story "The Collector". In this sense, this paper aims to investigate, through classical theoretical literary postulates, the way in which Rubem Fonseca constructs this figure in one of his most emblematic texts.